NFIL3 and its immunoregulatory role in rheumatoid arthritis patients - Du, Juping; Zheng, Liyuan; Chen, Shuaishuai; Wang, Na; Pu, Xia; Yu, Die; Yan, Haixi; Chen, Jiaxi; Wang, Donglian; Shen, Bo; Li, Jun; Pan, Shaobiao (Frontiers in Immunology, 2022)
Nuclear-factor, interleukin 3 regulated (NFIL3), an immune regulator, has played an essential role in autoimmune disease. However, the relationship between RA and NFIL3 remains largely unknown. In this study, we aimed to explore NFIL3 expression in RA patients and its potential molecular mechanisms. Increased NFIL3 expression was identified in PBMCs from 62 naïve RA patients and 75 healthy controls (HC) by quantitative real-time PCR (qRT-PCR). No correlation between NFIL3 and disease activity was observed. In addition, NFIL3 was significantly upregulated in RA synovial tissues analysed from the Gene Expression Omnibus (GEO) dataset (GSE89408). Then we classified synovial tissues into NFIL3-high (≥75%) and NFIL3-low (≤25%) group according to NFIL3 expression levels. Totally, 405 differentially expressed genes (DEGs) were screened out between NFIL3-high and NFIL3-low group using the “limma” R package. Enrichment analysis showed that most of the enriched genes were primarily involved in TNF signaling pathway via NFκB, IL-17 signaling pathway and rheumatoid arthritis pathways. Then, ten genes (IL6, IL1β, CXCL8, CCL2, PTGS2, MMP3, MMP1, FOS, SPP1, ADIPOQ) were identified as hub genes, and most of them play a key role in RA. NFIL3-related PPI network was performed using STRING database and four clusters (mainly participate in inflammatory response, lipid metabolism process, extracellular matrix organization and circadian rhythm) were constructed with MCODE in Cytoscape. Furthermore, 29 DEGs was overlapped with RA-related genes from RADB database, and were mainly enriched in IL-17 signaling pathways. Thus, our study revealed elevated expression of NFIL3 both in RA peripheral blood and synovial tissues and the high expression of NFIL3 correlated with the abnormal inflammatory cytokines and inflammatory response, which potentially contributed to RA progression.